Dose-Dependent Efficacy of Aripiprazole in Treating Patients With Schizophrenia or Schizoaffective Disorder: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Qian, Li; Xuemei, Liao; Jitao, Li; Yun'Ai, Su; Tianmei, Si (Frontiers in Psychiatry, 2021)
Purpose: To compare the efficacy and tolerability of different administration strategies of aripiprazole. Methods: We searched MEDLINE, EMBASE, the Cochrane Central, Web of Science, China National Knowledge Infrastructure(CNKI), and Wanfang Data Knowledge Service Platform(Wanfang) for randomized controlled trials (RCTs) of aripiprazole, using the terms: (aripiprazole) AND (schizophr* OR schizoaff*) AND (“syndrome scale” OR PANSS) AND (clini* OR trial). We retrieved study design, participant characteristics, comparison groups, and outcomes from each study. Results: In total, nine RCTs were selected for meta-analysis, which covered approximately 1,187 participants. We defined two treatment groups that represent different treatment strategies: (1) the high-dose group (the high-dose strategy) rapidly increased to doses higher than 15 mg/day in 2 weeks or began with doses higher than 15 mg/day, otherwise the group was defined as (2) the low-dose group (the low-dose strategy). If the initial or target doses of aripiprazole in a study were all higher than 15 mg/day, the high- and low-dose groups were created based on the relative level of the dose. The high-dose group showed significantly greater reductions in Positive and Negative Syndrome Scale (PANSS) total scores (standardized mean differences = -8.31, 95% confidence interval [CI] = -16.48, -0.13; P < 0.01; I2 = 96%) than the low-dose group. The high-dose group showed superior effects compared with the low-dose group in long-term studies (more than 8 weeks) (standardized mean differences = -13.81, 95% CI = -25.07, -2.55; P < 0.01; I2 = 96%). With exception of somnolence, we did not find significant differences in side effects or discontinuation due to adverse events. Sensitivity analyses produced similar results. Conclusion: The high-dose treatment strategy of aripiprazole for patients with schizophrenia or schizoaffective disorder may bring more benefits without obvious side effects.